Soil microbial community assembly and stability are associated with potato (Solanum tuberosum L.) fitness under continuous cropping regime - Gu, Songsong; Xiong, Xingyao; Tan, Lin; Deng, Ye; Du, Xiongfeng; Yang, Xingxing; Hu, Qiulong (Frontiers in Plant Science, 2022)
Continuous cropping obstacles caused by the over-cultivation of a single crop trigger soil degradation, yield reduction and the occurrence of plant disease. However, the relationships among stability, complexity and the assembly process of soil microbial community with continuous cropping obstacles remains unclear. In this study, molecular ecological networks analysis (MENs) and inter-domain ecological networks analysis (IDENs), and a new index named cohesion tools were used to calculate the stability and complexity of soil microbial communities from eight potato cultivars grown under a continuous cropping regime by using the high-throughput sequencing data. The results showed that the stability (i.e., robustness index) of the bacterial and fungal communities for cultivar ZS5 was significantly higher, and that the complexity (i.e., cohesion values) was also significantly higher in the bacterial, fungal and inter-domain communities (i.e., bacterial-fungal community) of cultivar ZS5 than other cultivars. Network analysis also revealed that Actinobacteria and Ascomycota were the dominant phyla within intra-domain networks of continuous cropping potato soil communities, while the phyla Proteobacteria and Ascomycota dominated the correlation of the bacterial-fungal network. Infer community assembly mechanism by phylogenetic-bin-based null model analysis (iCAMP) tools were used to calculate the soil bacterial and fungal communities’ assembly processes of the eight potato cultivars under continuous cropping regime, and the results showed that the bacterial community was mainly dominated by deterministic processes (64.19% - 81.31%) while the fungal community was mainly dominated by stochastic processes (78.28% - 98.99%), indicating that the continuous-cropping regime mainly influenced the potato soil bacterial community assembly process. Moreover, cultivar ZS5 possessed a relatively lower homogeneous selection, and a higher TP, TN, AP and yield than other cultivars. Our results indicated that the soil microbial network stability and complexity, and community assemble might be associated with yield and soil properties, which would be helpful in the study for resistance to potato continuous cropping obstacles.